PENGARUH PERENCANAAN KARIR TERHADAP KINERJA BISNIS LAYANAN KANTOR MELALUI MOTIVASI KERJA DI DIVISI HUMAN CAPITAL SERVICE PT TELKOM INDONESIA GRAHA MERAH PUTIH - Muhammad Farhan Badruzzaman, - (2022)
The background raised in this study is the optimal performance of employees at PT. Telkom Indonesia Tbk. Graha Merah Putih Human Capital Service Division. Employee performance can also be influenced by several factors, one of which is by career planning through work motivation. The purpose of this study is to find out the level of effectiveness of career planning of employees in the Human Capital Service Division of PT Telkom Indonesia Graha Merah Putih, the high performance of office business services in the Human Capital Service Division of PT Telkom Indonesia Graha Merah Putih, the level of motivation for the work of employees in the Human Capital Service Division of PT Telkom Indonesia Graha Merah Putih, The influence of Career Planning on work motivation in the Human Capital Service Division of PT Telkom Indonesia Graha Merah Putih, Is the influence of Career Planning on the performance of office business services in the Human Capital Service Division of PT Telkom Indonesia Graha Merah Putih, and Is the influence of Planning. The method used in this study is a survey method and to answer the problem formulation in this study using descriptive analysis techniques and inferential analysis techniques. The population in the study was 34 respondents from employees in the Human Capital Service Division. The techniques used in this study are simple regression and sobel tests. The results showed that career planning is in the category of enough, employee performance is in the category enough, and work motivation is in the category enough. Hypothesis test results show that career planning has a partially positive effect on employee performance through work motivation. The results of the correlation coefficient values state that the correlation in career planning to performance is in the low category, while in the employee performance variable through work motivation is in the high category. Thus employee performance can be improved by good career planning and through work motivation.